Aktivitas antioksidan dalam olahan makanan terfortifikasi tepung daun kelor (moringa oleifera) sebagai upaya pencegahan stunting - Widowati, Hesty; Budiandari, Rahmah Utami; Hanum, Sri Mukhodim Faridah; Kartikasari, Dwi Ajeng (ARGIPA (Arsip Gizi dan Pangan), 2023)
Moringa (Moringa Oleifera) is a food that has a million health benefits. The high content of nutritional value and bioactive compounds in Moringa can be used as an alternative food ingredient that can overcome and prevent malnutrition and stunting in children under five. The purpose of this study was to determine differences in antioxidant levels in foods made from moringa leaves (moringa nuget and moringa pudding). This study used a two-factor nested design. Factor 1 was the type of processed moringa, namely (P1) chicken nuget and (P2) pudding and the second factor was the concentration of the addition of moringa (K1) the addition of 5% moringa, (K2) the addition of 10% moringa, (K3) the addition of 15% moringa. So that 6 treatments were obtained and repeated 4 times so that 24 experimental units were obtained. The research method uses nested method analysis with α of 5%. Data analysis used Minitab 17 and Microsoft Excel 2013 software. The results of the analysis showed P 1.00 > 0.05, meaning that the effect was not significant on the antioxidant levels of processed moringa products. The IC50 value of each processed moringa nuget and pudding showed that the higher the antioxidant value was inversely proportional to the antioxidant activity. It can be concluded that in processed nuget, the best antioxidant activity was at a highest concentration of 15%, while in Moringa pudding at a lowest concentration of 5%.